PROBLEMATIKA PEMBELAJARAN BERBASIS PROJECT PADA MATA PELAJARAN PPKN DI JENJANG PENDIDIKAN DASAR - Fadillah, Randy; Saputra, Kosasih Adi; Paturochman, Iwan Ridwan; Sirait, Budi Chrismanto (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. This research identifies several problems in the implementation of project-based learning at the basic education level, especially in the subject of Pancasila and Civic Education (PPKn). One of the problems that arises is the limited learning time. Project-based learning requires more time, as students have to develop their projects gradually. To overcome this problem, it is necessary to identify efficient ways to organize learning time and resources. Lack of student engagement is also an issue. Lack of motivation, skills or previous experience in project-based learning can lead to low student engagement. Therefore, more engaging learning strategies that focus on students' interests and provide appropriate support are needed to overcome these barriers. This research was conducted using a qualitative approach, by collecting data from interview scripts, field notes, personal documents, memo notes, and official documents. The focus of this research is the project-based learning process in Civics subjects at the primary education level. The steps of data analysis include data reduction, categorization, presentation, and conclusion making. Thus, this research aims to provide better insights in overcoming problems in project-based learning at the primary education level. Keywords: Project-based Civics, Project-based Learning Methods, Project Citizen.